Financial practices and physical health influencing financial health of Malaysian employees - Abdul Rahim @ Abdul Wahab, Husniyah; Sabri, Mohamad Fazli; S., Norhasmah; Othman, Mohd Amim; S., Norhafifah; Mat Rahim, Fatin Farwizah (Malaysian Consumer and Family Economics Association, 2017)
Individuals make financial decisions throughout their working days to be financially well. Physical health and financial health of individual may be interrelated and determined the choice of financial practices that they performed. This study aimed to identify the interrelation between financial practices, physical health and financial health of employees. Important factors affecting financial health of employees are also identified. Prior to these, the employees’ levels of financial practices, health risks and financial health were determined. Four states selected from four zones in Peninsular Malaysia were sampled via multistage random sampling to obtain a target of 500 respondents. Selected agencies in those states were contacted to appoint liason officers who facilitated the data collection processes. Self-administered questionnaires distributed through them resulted in only 356 usable questionnaires. Findings revealed that among the financial practices, only investment was found to be not significantly correlated with financial health, however the regression results revealed that only savings was found to be influencing financial health. This reflected that other financial practices were not as important as savings to the financial health. Health risks were prevalent from the physical and mental measures of health with PCS and MCS slightly below the border of 50 while financial health was slightly above the midpoint of its scale. Older employees with higher income were revealed to have better financial health as compared to younger and lower income employees. Furthermore, only physical measure of health significantly influenced financial health but not mental health. As majority of these employees were young, the health risks may pose a risk on their job productivity and the impact on the quality of public services. Thus, it is critical for the government to forsee these health risks and financial health situation of their employees to ensure better outcomes for the public and country.